LEARNING ARABIC TRANSLATION AT ISLAMIC BOARDING SCHOOL IN MADURA - Mahbubah, Latifatul; Biahmada, Ahmad Mufatis Maqdum; Mauludiyah, Lailatul (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
The study aimed to describe the method of learning turats book with a translation model in al-Amin Islamic boarding schools. This research was conducted using a qualitative approach with the process of analysis deductively. The process of data retrieval was based on direct observation of the learning process in Ma?had Al-Amin. The results of this study were the process of learning turats book material using the Harfiyah translation or literal translation process. The learning process is supported by the existence of ?syamil? book which contains of material on qawaid. With the existence of the book, students were able to translate books containing subject matter with the help of the book of syamil. Therefore, the purpose of learning can be directly conveyed and students' understanding of qawaid translation if it can be done outside the classroom.